2021
DOI: 10.1111/jcpt.13526
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a web‐based educational programme for pharmacists during the COVID‐19 pandemic in Japan

Abstract: What is known and Objective Continuing education is essential for pharmacists to acquire and maintain the knowledge, skills, and ethical attitudes necessary for clinical practice. However, with the emergence of COVID‐19, the social circumstances and face‐to‐face learning environments have changed. The objectives of this study were to determine Japanese pharmacists’ perception of a web‐based educational programme in oncology, and assess changes in their understanding of pharmaceutical care in oncology before an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Regular research conferences have been reported as a critical factor in research activities by resident physicians [ 9 ]. Moreover, as several reports have shown the usefulness of web-based educational programs received by community and hospital pharmacists [ 10 , 11 ], web-based workshops may be useful depending on the level of achievement.…”
Section: Discussionmentioning
confidence: 99%
“…Regular research conferences have been reported as a critical factor in research activities by resident physicians [ 9 ]. Moreover, as several reports have shown the usefulness of web-based educational programs received by community and hospital pharmacists [ 10 , 11 ], web-based workshops may be useful depending on the level of achievement.…”
Section: Discussionmentioning
confidence: 99%